Antimicrobial activity of photosensitizers: arrangement in bacterial membrane matters - Batishchev, Oleg V.; Kalutskii, Maksim A.; Varlamova, Ekaterina A.; Konstantinova, Anna N.; Makrinsky, Kirill I.; Ermakov, Yury A.; Meshkov, Ivan N.; Sokolov, Valerij S.; Gorbunova, Yulia G. (Frontiers in Molecular Biosciences, 2023)
Porphyrins are well-known photosensitizers (PS) for antibacterial photodynamic therapy (aPDT), which is still an underestimated antibiotic-free method to kill bacteria, viruses, and fungi. In the present work, we developed a comprehensive tool for predicting the structure and assessment of the photodynamic efficacy of PS molecules for their application in aPDT. We checked it on a series of water-soluble phosphorus(V) porphyrin molecules with OH or ethoxy axial ligands and phenyl/pyridyl peripheral substituents. First, we used biophysical approaches to show the effect of PS on membrane structure and their photodynamic activity in the lipid environment. Second, we developed a force field for studied phosphorus(V) porphyrins and performed all-atom molecular dynamics simulations of their interactions with bacterial lipid membranes. Finally, we obtained the structure-activity relationship for antimicrobial activity of PS and tested our predictions on two models of Gram-negative bacteria, Escherichia coli and Acinetobacter baumannii. Our approach allowed us to propose a new PS molecule, which MIC50 values after extremely low light dose of 5 J/cm2 (5.0 ± 0.4 μg/mL for E. coli and 4.9 ± 0.8 μg/mL for A. baumannii) exceeded those for common antibiotics that makes it a perspective antimicrobial agent.